Integrated stratigraphy across the Aptian/Albian boundary at Col de Pré-Guittard (southeast France) : a candidate global boundary stratotype section - W. J. Kennedy; A. S. Gale; B. T. Huber; P. Bown; H. C. Jenkyns; M.R. Petrizzo; A. Barchetta (Cretaceous Research, 2014)
The outcrop of the Marnes Bleues at the Col de Pré-Guittard, 11km north of the village of Rémuzat in the Départment of DrÔme in southeastern France is probably the most intensively studied succession spanning the Aptian/Albian boundary interval. Following the rejection of the proposed GSSP for the base of the Albian Stage (based on the first occurrence of the ammonite Leymeriellla tardefurcata in the section at Le Pillart, Tartonne, Alpes-de-Haute Provence), we re-visit the Pré-Guittard section. A new candidate GSSP defined by the first occurrence of the planktonic foraminifera Microhedbergella renilaevis Huber and Leckie, 2011 is here proposed. This first occurrence is placed in a 100m section with 28 secondary markers, including calcareous nannofossils, planktonic foraminifera, palynomorphs, an inoceramid bivalve, ammonites, stable carbon isotopes, and local marker beds. The outcrop fulfils most of the physical criteria required of a Global Stratotype Section and Point. © 2014 Elsevier Ltd.